Perbandingan trajectory tracking pada prototype excavator sistem pneumatic dengan sistem kontrol menggunakan joystick dan smartphone android - Randis Randis; Angga Wahyu Aditya (Universitas Muhammadiyah Metro, 2019)
Trajectory tracking testing is mostly implemented both on vehicles, mobile robots, flying robots, and excavators to generate a small value of trajectory tracking to effectiveness and efficiency by the tasks and functions of each unit or product. This study aims to compare trajectory tracking on pneumatic excavator units with a manual control system with a joystick and a remote control system using an Android smartphone. Two tracks are used where the first track uses combine straight and radius shapes and the second track combines horizontal and vertical lines that form an angle of 90º. The results showed the use of remote control using an Android smartphone still has a higher trajectory tracking error when compared to manual control with a joystick even though on average the error results obtained are small, so more remote control is needed. Keywords: Pneumatic excavator system, joystick control system, remote control system, error trajectory tracking.